THE ROLE OF PHRASEOLOGICAL UNITS IN POLITICAL MEDIA TEXTS («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In the realm of political discourse, language serves as a powerful tool for conveying ideas, shaping narratives, and influencing public opinion. Within this context, phraseological units play a significant role in political media texts by encapsulating complex concepts, creating rhetorical impact, and reinforcing specific ideologies. This article explores the importance of phraseological units in political communication, highlighting their usage in newspapers and journals to illustrate how these linguistic devices contribute to the construction of persuasive messages and the dissemination of political agendas.
Keywords: фразеологизмы, политические медиатексты, политическая коммуникация, политический дискурс.